2021
DOI: 10.1097/aud.0000000000001163
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Influences on Hearing in Adulthood: a Systematic Review and Two-Step Individual Patient Data Meta-Analysis

Abstract: Objectives: Adverse prenatal and early childhood development may increase susceptibility of hearing loss in adulthood. The objective was to assess whether indices of early development are associated with adultonset hearing loss in adults ≥18 years.Design: In a systematic review and meta-analysis, four electronic databases were searched for studies reporting associations between indices of early development (birth weight and adult height) and adult-onset hearing loss in adults ≥18 years. We screened studies, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 67 publications
(121 reference statements)
0
9
0
Order By: Relevance
“…Of the 17 included SRs, 10 considered physiological risk factors for hearing loss [38][39][40][41][42][43][44][45][46][47], four considered environmental risk factors [52][53][54], two considered demographic risk factors [49,50], and one considered behavioral risk factors [48]. Of the 251 primary studies, 248 were observational studies, and three were RCTs.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 17 included SRs, 10 considered physiological risk factors for hearing loss [38][39][40][41][42][43][44][45][46][47], four considered environmental risk factors [52][53][54], two considered demographic risk factors [49,50], and one considered behavioral risk factors [48]. Of the 251 primary studies, 248 were observational studies, and three were RCTs.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…All 17 SRs included studies which reported gender and personal characteristics at baseline, and 15 SRs included studies which reported gender and personal characteristics in the analysis of results, although in some reviews the latter was in a small proportion of included studies [38,[41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Studies reporting data on occupation were included in a total of eight SRs [38,42,45,48,49,51,53,54]. Place of residence, race/ethnicity, education, socioeconomic status, social capital and features of relationships were also reported across the included studies, albeit in fewer than 10% of studies at both baseline and in results for all criteria.…”
Section: Observational Studiesmentioning
confidence: 99%
See 3 more Smart Citations